2014
DOI: 10.1111/sms.12217
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular adaptations to 4 and 12 months of football or strength training in 65‐ to 75‐year‐old untrained men

Abstract: The study examined the effects of 1 year of football or strength training on cardiovascular function in 65-to 75-year-old men. Twenty-six untrained men (age: 68.2 ± 3.2 years) were randomized to football training (FTG; n = 9), strength training (STG; n = 9), or control (CG; n = 8). In FTG, left ventricular (LV) internal diastolic diameter, end-diastolic volume, and mass index were 8%, 21%, and 18% higher (P < 0.01), respectively, after 12 months, with no changes in STG and CG. After 12 months, LV ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(110 citation statements)
references
References 41 publications
6
100
3
1
Order By: Relevance
“…football clubs, stadia) may facilitate health promotion in men , including older men Bingham et al 2014;Parnell et al 2015;Schmidt et al 2014), the active construction of a particular form of masculinity emphasising competition, aggression, and personal dominance over others may exclude other 'non-hegemonic' men (Robertson 2003;Spandler and McKeown 2012). These can include OM, who often find difficulties in joining the competitive performance of team sports and may feel anxious about engaging in sports .…”
Section: Introductionmentioning
confidence: 99%
“…football clubs, stadia) may facilitate health promotion in men , including older men Bingham et al 2014;Parnell et al 2015;Schmidt et al 2014), the active construction of a particular form of masculinity emphasising competition, aggression, and personal dominance over others may exclude other 'non-hegemonic' men (Robertson 2003;Spandler and McKeown 2012). These can include OM, who often find difficulties in joining the competitive performance of team sports and may feel anxious about engaging in sports .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication from the present study cohort, ST was found to be experienced by patients as a feasible and enjoyable exercise modality that was associated with a sense of regained control over their health and promotion of a mutually caring behaviour between subjects [16] [50]. Although we observed a number of musculoskeletal injuries, such injuries must be weighed against the psychological benefits and the detrimental effects of physical inactivity and consequent morbidity and mortality.…”
Section: Discussionmentioning
confidence: 48%
“…invasive protocols or ultrasound measurements of flow-mediated vasodilation of the brachial artery [16] [33]. Microvascular endothelial function has been suggested to be more sensitive to cardiometabolic risk factors e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations